PENERAPAN MODEL MAKE A MATCH BERBANTUAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPAS PADA SISWA KELAS III SD NEGERI PANAIKANG KABUPATEN GOWA - Herawaty Syam; Andi Makkasau; Widya Karmila Sari Ahmad (STKIP Subang, 2026)
This research is motivated by the low cognitive learning outcomes of IPAS among third-grade students at Panaikang State Elementary School, Gowa Regency. This study aims to improve these learning outcomes through the application of the Make a Match model assisted by Flashcard media. This research is a Classroom Action Research (CAR) conducted in two cycles, where each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects were 30 people. Data collection techniques used were observation, testing, and documentation, while the data were analyzed using quantitative and qualitative descriptive analysis techniques. In cycle I, the results of observations on the learning process were in the Sufficient (C) category and the results of the cognitive learning test were in the Sufficient (C) category. Meanwhile, in cycle II, the results of observations on the learning process improved to the Good (B) category and the results of the cognitive learning test also reached the Good (B) category. The conclusion of this study is that the application of the Make a Match model assisted by Flashcard media can improve the cognitive learning outcomes of IPAS among third-grade students at Panaikang State Elementary School, Gowa Regency.